2000
DOI: 10.1021/bi991631c
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Mutational Mapping of Sites on Human Interferon-β-1a That Are Important for Receptor Binding and Functional Activity

Abstract: A systematic mutational analysis of human interferon-beta-1a (IFN-beta) was performed to identify regions on the surface of the molecule that are important for receptor binding and for functional activity. The crystal structure of IFN-beta-1a was used to design a panel of 15 mutant proteins, in each of which a contiguous group of 2-8 surface residues was mutated, in most instances to alanine. The mutants were analyzed for activity in vitro in antiviral and in antiproliferation assays, and for their ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 58 publications
4
75
0
Order By: Relevance
“…PEGylated Interferon ␤-1a Pharmacology and Toxicology 993 ing site (Karpusas et al, 1998;Runkel et al, 2000;Baker et al, 2006). Using the same site-specific N-terminal PEGylation procedure, a similar PEG-IFN ␤-1a molecule has been synthesized previously with 20-kDa mPEG-propionaldehyde.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEGylated Interferon ␤-1a Pharmacology and Toxicology 993 ing site (Karpusas et al, 1998;Runkel et al, 2000;Baker et al, 2006). Using the same site-specific N-terminal PEGylation procedure, a similar PEG-IFN ␤-1a molecule has been synthesized previously with 20-kDa mPEG-propionaldehyde.…”
Section: Discussionmentioning
confidence: 99%
“…PEG-conjugated (PEGylated) IFN ␤-1a (PEG-IFN ␤-1a) was developed by attaching 20-kDa methoxy-PEG-O-2-methylpropionaldehyde to the ␣-amino group of the N terminus of IFN ␤-1a (Baker et al, 2006), with the aim of providing a less frequent dosing regimen and improved convenience for patients with MS. The N terminus of IFN ␤-1a is not critical for binding to the type 1 IFN receptor (Runkel et al, 2000). In vitro evaluation demonstrated that PEG-IFN ␤-1a retained significant in vitro activity (approximately 50%) in antiviral and antiproliferative assays compared with the unmodified protein, whereas PEG-IFN ␤-1a in vivo efficacy was enhanced compared with IFN ␤-1a in a mouse tumor angiogenesis model (Baker et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In light of our findings, it was interesting to reanalyze the work of Runkel et al (44) describing the loss of IFN-␤-specific activities for mutants with mutations at positions 86 and 92. These mutations, which are located at the IFNAR1 binding site on interferon (20,40,43), apparently reduce the binding affinity for IFNAR1, and hence it is not surprising that the mutants now have the characteristics of IFN-␣. Our data also demonstrate that the binding affinity towards IFNAR1 is directly related to the antiproliferative activity of IFN.…”
Section: Discussionmentioning
confidence: 99%
“…The Dhelix is not directly involved in receptor binding, and amino-acid substitutions have been made in this region without affecting the activity of the overall molecule. 16 We have identified amino acids within this peptide epitope as critical for the in vitro proliferative response. Multiple changes could be made in this region that could potentially reduce T-cell responses with minimal disruption to bioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, multiple alanine-substituted peptides were constructed that were based on published sequences, where the changes coincided with the discovered epitope regions, but did not significantly affect the activity of the mutated IFN-b molecule. 16 A set of 103 community donors was tested with the parent and modified epitope regions (Figure 2). This set of donors is independent of the original set of 87 donors tested with the IFN-b peptide set reported in Figure 1a.…”
Section: Critical Residue Determinationmentioning
confidence: 99%